Agent Based Individual Trafficguidance - Wanscher, Jørgen Bundgaard (Proceedings from the Annual Transport Conference at Aalborg University, 2006)
When working with traffic planning or guidance it is common practice to view the vehicles as a combined mass. From this models are employed to specify the vehicle supply and demand for each region. As the models are complex and the calculations are equally demanding the regions and the detail of the road network is aggregated. As a result the calculations reveal only what the mass of vehicles are doing and not what a single vehicle is doing. This is the crucial difference to Agent Based Individual Traffic guidance (ABIT). ABIT is based on the fact that information on the destination of each vehicle can be obtained. This information can then be used to provide individual traffic guidance as opposed to the mass information systems of today – dynamic road signs and traffic radio. The goal is to achieve better usage of the road and time. The main topic of this paper is the current development in both practical and theoretical fields concerning the realization of ABIT.